An evaluation of paediatric medicines reconciliation at hospital discharge into the community. (16th December 2015) - Huynh, Chi; Wong, Ian Chi Kei; Tomlin, Stephen; Halford, Ellisha; Jani, Yogini; Ghaleb, Maisoon
Abstract: Objective: A UK national survey of primary care physicians has indicated that the medication information on hospital discharge summary was incomplete or inaccurate most of the time. Internationally, studies have shown that hospital pharmacist's interventions reduce these discrepancies in the adult population. There have been no published studies on the incidence and severity of the discrepancies of the medication prescribed for children specifically at discharge to date. The objectives of this study were to investigate the incidence, nature and potential clinical severity of medication discrepancies at the point of hospital discharge in a paediatric setting. Methods: Five weeks prospective review of hospital discharge letters was carried out. Medication discrepancies between the initial doctor's discharge letter and finalised drug chart were identified, pharmacist changes were recorded and their severity was assessed. The setting of the review was at a London, UK paediatric hospital providing local secondary and specialist tertiary care. The outcome measures were: – incidence and the potential clinical severity of medication discrepancies identified by the hospital pharmacist at discharge. Key findings: 142 patients (64 female and 78 males, age range 1 month – 18 years) were discharged on 501 medications. The majority of patients were under the care of general surgery and general paediatric teams. One in three discharge letters contained at least one medication discrepancy and required pharmacist interventions to rectify prior to completion. Of these, 1 in 10 had the potential for patient harm if undetected. Conclusions: Medicines reconciliation by pharmacist at discharge may be a good intervention in preventing medication discrepancies which have the potential to cause moderate harm in paediatric patients.